Study of the concentration level of heavy metals in water and some tissues of common carp, Carpinus carpio L. which is cultured in cages in the Euphrates River - Jasim, Ruaa Mohammed; Kamil Kadhim Fahad (University of Thi-Qar Journal of agricultural research, 2023)
The current study included measuring some chemical and physical properties of the water of the study area and estimating the concentration of three heavy elements (lead, copper, and zinc) in the tissues of the common carp (Gills, muscles, and viscera) of Cyprinus carpio L. Samples were collected from one of the private farms that raise fish in floating cages on the Euphrates River from 11/18/2022 to 4/18/2023. The study also included measuring water temperature, air, turbidity, electrical conductivity, total dissolved solids, pH And dissolved oxygen samples taken from the water were analyzed as well as samples taken from fish tissues on a monthly basis. The results of the study showed that the air temperature ranged between(6.8-10.2)C. Water temperature (17_33), turbidity (6.8_10.2), electrical conductivity (1.04_2.13), total dissolved solids (7752_18730) mg/l, and pH value (7.2_7.82) between neutral to lightly basic. The dissolved oxygen value ranged between (6.78 - 7.92) mg/l during the months of the experiment. The standard methods were used to estimate the concentration of heavy metals in water and tissues by flame atomic absorption spectrometer. The results showed that the highest total concentration of lead, copper and zinc was recorded in the water during the winter season (1.533, 2.300, 6.700) µg/L. Recorded in tissues for lead in the gills and viscera, the highest values were in spring (9.533, 6.500) µg/L, respectively. Copper recorded the highest value in the gills and viscera, respectively, and the concentrations were high in the autumn season (16.793, 18.723) µg/g dry weight, respectively. g dry weight respectively, the results showed that the accumulation of heavy elements was in the following order . Concentrations in the water are zinc < copper < leadAnd in the tissue as follows Gills < muscle < viscera lead gills < viscera < muscle copper Zinc gills < muscle < visceraDifferent densities were also studied to obtain the best culture density. Three densities (21_25_28 fish / m3) were used, with 500 fish for the first treatment, 900 fish for the second treatment, and 1100 fish for the third treatment, with an average weight of (120_140) g. Diet of Iranian origin was used for the three treatments. The results of the statistical analysis showed that there were significant differences during the months of the study, where the highest rate was in the month of March.